Treatment plan dosimetric impact after catheter stretch during multi-catheter interstitial breast brachytherapy - Boman, Eeva; Paterson, Dean; Huang, Junou; Pearson, Shelley; Johnson, Carol (Journal of Contemporary Brachytherapy, 2017)
Purpose: Nylon 6/6 interstitial brachytherapy catheters may stretch when exposed to moisture, mechanical tension, and body temperature. The purpose of this study is to evaluate the magnitude of catheter stretch during a course of multi-catheter interstitial breast brachytherapy for nylon 6/6 treatment catheters, and to assess the impact this has on treatment plan dosimetry. Material and methods : Catheters were exposed to water at 37°C for six days and the internal catheter length change (∆L_W) was measured daily. Additionally, the measured internal catheter length change (∆L_P), performed prior to each treatment fraction, for seven interstitial breast brachytherapy patients (total of 76 catheters) were retrospectively analyzed. The maximum length change seen in ∆L_P and ∆L_W were introduced as a source positional error to retrospective treatment plans, and treatment plan dosimetry was analyzed. Results : ∆L_W and ∆L_P were on average +4.0% and +1.6% of the catheter lengths in water or tissue after 48 hours. Weak correlation was seen between the average ∆L_P per catheter and both the catheter length within tissue (ρ = 0.36, p = 0.0007), and the mid-catheter depth in tissue (ρ = 0.42, p < 0.0001). The D90CTV decreased 1.5% (p < 0.05) and 8.2% (p < 0.05) when the ∆L_P and ∆L_W were introduced to the initial plans. Conclusions : Nylon 6/6 catheters stretch during a course of multi-catheter interstitial breast brachytherapy treatment. The observed stretch may affect treatment plan dosimetry, if the catheter internal length is only measured immediately after the insertion. Additional catheter length checks are recommended to verify the actual catheter internal length during the treatment.